Poetry of Kazi Nazrul Islam in English translation. Volume 1 - Nazrul Islam, Kazi, 1899-1976.; Huda, Muhammad Nurul; Nazrul Institute (Dhaka, Bangladesh) (Dhaka : Nazrul Institute, 1997)
Complete works by a 20th century Bengali poet.
English and Bengali.
Keywords: Nazrul Islam, -- Kazi, -- 1899-1976 -- Translations into English